Landsmann Solidarity among Turkish Citizens. (21st May 2015) - Caya, Sinan
Abstract: Compatriotship, favoring one's townspeople (Landsmann), is a special kind of nepotism prevailant in Turkish society. People from the same geographical region do come together and enjoy solidarity when they meet one another elsewhere. The idea of belonging carries strong burdens of responsibility along with it. The concept is of feudal nature and is loosening with modernization. Interestingly, compatriotship does not necessarily include favoring his own ethnicity. It also cuts throgh social classes, as well.